Koyaanisqatsi : life out of balance - Reggio, Godfrey; Glass, Philip; MGM Home Entertainment Inc. (Santa Monica, CA : MGM Home Entertainment, 2002)
Presents images of a world living outside its means, without structure or discernable pattern and explores the contrast and collision between urban life, technology, and the environment.
Features: interview with director and composter, trailer for the qatsi trilogy.
Director of photography, Ron Fricke; editors, Alton Walpole and Ron Fricke; music, Philip Glass.
Not rated.
DVD, Dolby digital 5.1 surround.
Keywords: Environmental impact analysis; Experimental films; Documentary films